Motivasi Menonton Si Bolang di Trans7 dalam Mendorong Anak untuk Bermain Aktif - Hapsari Putri Utami; Sri Budi Lestari (Interaksi Online, 2020)
The 'opiate' case against gadgets makes children to put aside their active playing. One of the children's television shows which to date shows active playing is show cased in the Si Bolang program on Trans7. Preliminary observations by researcher found that 5 out of 7 children who watched Si Bolang liked the playing scenes that were displayed. The playing scene that was aired by Si Bolang showed activities that require a lot of body movements. The study entitled "Motivation to Watch Si Bolang on Trans7 in Encouraging Children to Play Active" aims to find out what motivates children to watch Si Bolang and how children's motivation can encourage their desire to play active. Using descriptive qualitative research methods and a phenomenological approach that refers to the theory of motivation of someone using television by Alan Rubin (West & Turner, 2008: 102), divided into several categories such as pleasure, relaxation, and to learn certain content. Data collection is done by in-depth interviews with open-ended and using interview guides. The unit of analysis in this study uses techniques that refer to the analysis of phenomenological data. The results showed that children's motivation to watch television was only for relaxation. There are children who are compelled to watch television because of a motivating factor from outside themselves, that is from parents. However, when viewed from the child's motivation to watch television shows (Si Bolang on Trans7) for pleasure and to learn certain content. Child has their reasons for watching television and liking Si Bolang. In addition, not all children's motivation to watch Si Bolang can encourage children to play active. The limitation factor of the tool and knowing the scenes in Si Bolang shows that have been well prepared by the crew are the children's reasons why they don't imitate Bolang-style play active. Children imitate Bolang-style active play scenes using improvised tools and playing with their own way.